377Smoking, blood pressure, and body mass index to estimate healthy life expectancy: NIPPON DATA90. (2nd September 2021) - Tsukinoki, Rumi; Hayakawa, Takehito; Kadota, Aya; Murakami, Yoshitaka; Miura, Katsuyuki; Okayama, Akira; Okamura, Tomonori; Ueshima, Hirotsugu; ,
Abstract: Background: Healthy life expectancy (HLE) is an important measure of an ageing society. We estimated HLE based on combinations of smoking, blood pressure (BP), and body mass index (BMI) in the Japanese population using a multistate life table. Methods: A nationwide cohort study of Japan was performed using NIPPON DATA90 (N = 6, 676) with the Katz Activities of Daily Living Index as the HLE endpoint. Combinations of smoking (non-smokers and smokers), BP (2018 ESC/ESH Guidelines classification), and BMI (underweight, normal, and overweight) were developed, and the group-specific HLEs were calculated using a multistate life table. Results: At age 65, smokers had shorter HLE than non-smokers for all BMI and BP groups. The HLE of men who were overweight, hypertensive (Grade 2 or 3), and smokers was 14.05 years (95% confidence interval: 15.77-21.36); in contrast, the HLE of men who were normal weight, normotensive, and non-smokers was 19.04 years (16.46-21.61). Among all BMI and smoking status groups, HLE decreased linearly as BP increased regardless of sex. The HLE distribution showed a slight inverted U-shape as BMI increased in both sexes. Conclusions: This study showed that HLE at age 65 was considerably shorter in smokers and individuals with higher BP. Furthermore, both underweight and overweight had modest effects on HLE at age 65. Key messages: HLE was considerably shorter in smokers and individuals with higher BP. In addition, both underweight and overweight had modest effects on HLE.